ESTIMATION OF THE LOST CIRCULATION RATE USING FUZZY CLUSTERING OF GEOLOGICAL OBJECTS BY PETROPHYSICAL PROPERTIES - Efendiyev, G.; Mammadov, P.; Piriverdiyev, I.; Mammadov, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Currently, cluster-analysis or automatic classification problems are widely used in various fields, in particular economics, sociology, medicine, geology, and other sectors, where there are sets of arbitrary kinds of objects to be automatically divided into groups of similar objects based on their "similarities-differences" features. In recent years, these methods have been widely used in data analysis problems. Conventional methods of cluster-analysis suggest a clear partition of the original set into subsets, in which each point is included only in one cluster after the partition. However, it is well known that such a restriction is not always true. It is often necessary to make such kind of partition, which allows determining the degree of membership of each object for each set. In this case it is advisable to use fuzzy clusteranalysis methods. Problems in this formulation arouse interest of specialists dealing with geology, geophysics, oil- and gas-well drilling and oil and gas production. One of the most important results of the study of lost circulation zones is determination of the coefficient of lost circulation intensity. Purpose. Estimation of drilling mud lost circulation during drilling and emerging risks. Methodology. The solution of the problems posed in the work was carried out using methods known from mathematical statistics and the theory of fuzzy sets. The technique of processing the results, as well as fuzzy cluster analysis, was used for that purpose. Findings. As a result of the research, 5 classes were obtained, each of which characterizes the rate of mud lost circulation, expressed by linguistic variables. On the basis of this, fuzzy models are constructed, expressing the relationship between the indices of petrophysical properties and the volume of the absorbed solution. Originality. A method based on fuzzy cluster analysis has been developed, which makes it possible to predict drilling mud lost circulation of different rate at an early stage during drilling. Practical value. The obtained results allow making decisions on prevention of lost circulation and timely liquidation of their consequences.